Clinical and echocardiographic predictors of left atrial appendage dysfunction in patients with mitral stenosis in sinus rhythm - (:unkn) unknown (MOSBY, INC, 2004)
Background: Mitral stenosis (MS) causes left atrial (LA) appendage (LAA) dysfunction resulting in reduced LAA flow velocities. Low LAA peak emptying velocity (PEV), determined by transesophageal echocardiography, is a risk for thrombus formation and systemic embolism. Objective: We sought to investigate various clinical and echocardiographic predictors of low LAA blood flow velocities. Methods: A total of 44 patients with newly diagnosed MS were classified into two groups on the basis of the presence of high (PEV greater than or equal to 46 cm/s) or low (PEV < 46 cm/s) LAA flow profile on Doppler transesophageal echocardiography. LAA flow velocities were measured to be 27.38 +/- 8.17 cm/s in patients with LAA dysfunction and 70.75 +/- 16.71 cm/s in high-flow profile (P < .0001). Simultaneous 12-lead electrocardiogram was used to measure P waves. Results: P maximum, P dispersion, and LA diameter were significantly higher in patients with low LAA PEV (n = 32) than in those with high LAA PEV (111.87 +/- 16.93 vs 96.66 +/- 14.97, P = .0084; 73.12 +/- 20.7 vs 49.16 +/- 9.96, P < .0001; 46.06 +/- 4.384 vs 38.08 +/- 7.42 mm, P = .004; respectively). Patients with MS and low LAA blood flow had smaller mitral valve area compared with those with high LAA blood flow velocity (1.48 +/- 0.431 vs 1.85 +/- 0.442 cm(2), P = .02). Male sex, spontaneous echocontrast, and thrombus were more frequent in patients with low LAA PEV (7 [21.87%] vs 5 [41.66%], P = .026; 21 [65.62%] vs 4 [33.3%], P = .088; 4 [12.5%] vs none; respectively). Mild MS was more frequent in patients with high blood flow velocity {6 [27.2%] vs 14 [63.6%], P = .03}. Conclusion: At linear regression analysis, only P-wave dispersion and LA diameter predicted the LAA mechanical dysfunction reflected as low LAA PEVs.
Keywords: SPONTANEOUS ECHO CONTRAST; FIBRILLATORY WAVE AMPLITUDE; TRANSESOPHAGEAL ECHOCARDIOGRAPHY; FLOW-VELOCITY; THROMBOEMBOLISM; VALVULOPLASTY; MAINTENANCE; THROMBI; VALVE; RISK